Phytochemical study of the alkaloid from the bulbs of Eucharis grandiflora Planchon (Fam. Amaryllidaceae) - Sarmiento, Ma. Teresita R.; Santos, Rizalina B.; Concepcion. Adoracion B. (Quezon City: College of Pharmacy, University of the Philippines, 1983.)
The fresh bulb of Eucharis grandiflora Planchon of the Family Amaryllidaceae contains a greater amount of alkaloid than a dried sample. So far, there is no study and chemical investigation yet made on the alkaloid content of the bulb of this plant.
The present research work involved the extraction of alkaloid from the bulb of Eucharis grandiflora Planchon using a neutral solvent, ethanol. These alcohol extracts was analysed by precipitation with alkaloidal reagents, TLC and preparative TLC.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, October 1983.
Keywords: Plants -- Analysis; Amaryllidaceae; Amazon Lily